Kampanye Peningkatan Kesadaran Masyarakat sebagai Support System terhadap Penderita Depresi - Mulya, Nada Putri; Malik, Melani Raudatul (LaGeografia, 2020)
Depression is defined as a condition when people has a prolonged feeling of uselessness and a thought of suicide, and hard to expressed their feelings. Based on pre-research data, it was found that the age of 12 – 24 is an age where symptoms of depression appear, and potentially lead to suicide. This is due to the lack of literacy and public awareness of depression, which has eventually led to various stigma in public, thus cause the community's function as a support system was not going well. Communities in this case are people who are close to people with depression has strong influence to help them through the healing process. One important role of the community is providing accompaniment and mental support for people with depression, so they do not feel alone. Therefore, a good understanding and awareness is needed for the community to become a good support system for people with depression. In order to increase the public awareness and convey messages related to depression, the creator of the work did a campaign "Kenali Aku" that used The Nine Steps for Strategic Planning of Public Relations concept by Ronald D. Smith. This campaign has several activities such as education through social media, social experiment, and seminars (education that conducted in three regions in DKI Jakarta).